Peningkatan Kemampuan Mengenal Huruf Anak Usia Dini melalui Alphabet Book di Taman Kanak-kanak - Gusnita, Elvira; Hartati, Sri; Marlina, Serli (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The purpose of this study is to improve the ability to recognize children's letters through Alphabet Book. The type of research used is classroom action research with research subjects in class B of White Cambodia Kindergarten South Sumedang with a number of students of 15 people, 8 men and 7 women in the first semester of the 2018-2019 school year. This research was conducted with two cycles each cycle consisting of three meetings. In the first cycle of the third meeting, there was an improvement in the ability to recognize the letters of children with an average value of 49% after repairs in the third cycle of the third meeting had increased the ability to recognize letters with an average score of 85% which reached the minimum completeness criteria. Then it can be concluded that through Alphabet Book can improve the ability to recognize letters in children.